Applications of Recombinant DNA Technology in Gastrointestinal Medicine and Hepatology: Basic Paradigms of Molecular Cell Biology. Part C: Protein Synthesis and Post-Translational Processing in Eukaryotic Cells - Gary E Wild; Patrizia Papalia; Mark J Ropeleski; Julio Faria; Alan BR Thomson (Canadian Journal of Gastroenterology)
The translation of mRNA constitutes the first step in the synthesis of a functional protein. The polypeptide chain is subsequently folded into the appropriate three-dimensional configuration and undergoes a variety of processing steps before being converted into its active form. These processing steps are intimately related to the cellular events that occur in the endoplasmic reticulum and Golgi compartments, and determine the sorting and transport of different proteins to their appropriate destinations within the cell. While the regulation of gene expression occurs primarily at the level of transcription, the expression of many genes can also be controlled at the level of translation. Most proteins can be regulated in response to extracellular signals. In addition, intracellular protein levels can be controlled by differential rates of protein degradation. Thus, the regulation of both the amounts and activities of intracellular proteins ultimately determines all aspects of cell behaviour.